Is Moodle Gamification Effective in Reviewing Student's Motivation Related to Interest in Learning Online? - Kurnia Putri Sepdikasari Dirgantoro; Jessica Elfani Bermuli; Robert Harry Soesanto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to determine the effectiveness of Moodle gamification on students' learning motivation related to online learning interest. The research subjects were selected with a purposive sampling technique, namely the class of 2018 (n=112), class of 2019 (n=98), and class of 2020 (n=60). This study uses mixed methods. Quantitative data processing, using two-way Anova to see the main effect, interaction effect, and t-test to see a simple effect. The study finds that Moodle gamification is considered quite effective in motivating students regarding online learning interest. This result draws on survey data for 2018 2019 and 2020 students showing a “yes” answer to the question “Did gamification (e.g., level up, activity completion, and activity restriction) in Moodle motivate you during your major?” is 78.40%; 83.30%; and 90.91%. These results provide information that gamification increases student motivation. The implication of this study is that when the motivation of students is formed through gamification it will develop students' abilities.